Development of Kindergarten Child Stability Instruments - Mega Eni Lestari; Putu Aditya Antara; Putu Rahayu Ujianti (Indonesian Journal Of Educational Research and Review, 2021)
Lack of preparation and evaluation carried out by carrying out learning results in a decrease in the quality of student learning. The ability to stabilize children in the age range of 4-6 years is very important as they grow up. This study aims to develop an instrument for assessing the stability ability of children in Group B Kindergarten. This research is a development research with the RDR (Research, Development, Research) development model. This development research uses the developed RDR model, which includes three steps: product development, development, and effectiveness. Data collection techniques in this study were observation, interviews, and questionnaires. The instrument used in collecting data is a questionnaire. The technique used to analyze the data is qualitative and quantitative analysis. Based on the results of data analysis, the results of the validity and reliability of the instrument showed very high results. The value of the validity test is 0.92, and the reliability test is 0.80. Both scores are in the very high category. It indicates that the instrument has met the qualifications as a useful and appropriate instrument to use. This research implies that the instrument developed can be used as a guide in preparing early childhood learning assessments